PERAN PENDIDIKAN AGAMA ISLAM TERHADAP PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK - Novi Puspitasari; Linda Relistian. R; Reonaldi Yusuf (IAIN Bone, 2022)
This writing is presenting about the role of Islamic religious education on the formation of the religious character of students. Islamic religious education is an education that is very important and is considered effective in shaping the characteristics of students, specifically religious character. Where this religious character plays an important role in the lives of students both in the world and in the hereafter. Islamic religious education is the most important foundation of character education. Character education will grow and develop well if it starts from the embedded religious spirit in students, therefore Islamic religious education material in schools is one of the supporting characters for character education. Through Islamic religious education, students are taught aqidah as the basis of their religion, taught the Koran and hadith as guidelines and guidance to protect life. Therefore, the main purpose of Islamic religious education is to shape the personality of students which is reflected in behavior and mindset in everyday life. In addition, the success of learning Islamic religious education in schools is determined by the application of appropriate learning methods.